Studies On The Heterogenisation Of Sulphonic Acid And Guanidines On Silica And Their Catalytic Activity - Batagarawa, Muazu Samaila (2014)
The immobilization of three homogeneous catalysts namely; sulfonic acid, 1,1,3,3-tetramethyl guanidine and 1,5,7-triazabicyclo[4.4.0]dec-5-ene guanidine was carried out on silica from rice husk ash. Sodium silicate from the rice husk ash was immobilised with 3-(mercaptopropyl)trimethoxysilane. This was further oxidised to sulfonic acid in a simple one pot method. The solid acid catalyst was denoted as RHAPrSO3H. Analysis of the catalyst by nitrogen adsorption-desorption using Brunauer, Emmet and Teller (BET) method showed its surface area to be 340 m2g-1 with average pore volume of 0.24 cc g-1 and pore diameter of 2.9 nm. Acidity tests by cation exchange capacity and pyridine FT-IR adsorption, revealed the presence of acid sites on the catalyst surface. Similarly, the 29Si MAS NMR of RHAPrSO3H revealed the presence of Q4, Q3, T3, T2 and T1 silicon centres, while only Q4 and Q3 silicon centres were present in RHASiO2. The catalyst was used in the acetalization reaction of glycerol with benzaldehyde. Under the best reaction conditions of 120 °C temperature, 2:1 molar ratio of glycerol: benzaldehyde, 0.15g mass of catalyst and 8 h reaction time, significant conversion was achieved with high selectivity towards five member ring isomer.